Case report: A novel compound heterozygous variant in the TNXB gene causes single kidney agenesis and vesicoureteral reflux - Liang, Lei; Wu, Haotian; Meng, Haixia; Fu, Lin; Zhao, Jianrong (Frontiers in Endocrinology, 2024)
Primary vesicoureteral reflux (VUR) is the prevailing congenital anomaly of the kidneys and urinary tract, posing a significant risk for pyelonephritis scarring and chronic renal insufficiency in pediatric patients. Nevertheless, the precise genetic etiology of VUR remains enigmatic. In this current investigation, we conducted whole-exome sequencing on a child exhibiting single kidney, devoid of any familial VUR background, along with both biological parents. Two missense variants (NM_019105.8: exon11: c.4111G>A and NM_019105.8: exon2: c.31A>T) in the TNXB gene were identified through whole-exome sequencing of the child. These variants were found to be inherited from the child's parents, with each parent carrying one of the variants. Molecular dynamics simulations were conducted to assess the impact of these variants on the tenascin XB proteins encoded by them, revealing varying degrees of impairment. Based on our findings, it is suggested that the TNXB compound heterozygous variant, consisting of c.4111G>A and c.31A>T, may be the underlying cause of right renal agenesis and left hydronephrosis in afflicted child. This discovery broadens the genetic range of the TNXB gene and establishes a genetic foundation for disease-specific preimplantation genetic diagnosis (PGD) in prospective pregnancies involving the parents of this afflicted child.